A review on mobile cloud computing and issues in it - Hakak, Saqib Iqbal (Foundation of Computer Science, New York, USA, 2013)
Cloud computing is one of the emerging technology in this modern era. Some years back, this concept was related to only simple desktop computers or personal computers and static data centers and so on but now research is going on to implement this concept to mobiles also. So, in this paper, the concept of cloud computing as a general is given, followed by concept of mobile computing along with the general issues which are creating hindrances in completing this technology.